Atorvastatin-mediated downregulation of VCAM-1 and XO/UA/caspase 3 signaling averts oxidative damage and apoptosis induced by ovarian ischaemia/reperfusion injury - O. A. Afolabi; M. A. Hamed; D. C. Anyogu; D. H. Adeyemi; A. F. Odetayo; R. E. Akhigbe (Taylor & Francis Group, 2022)
Background Oxidative damage is critical in the pathogenesis of ovarian ischaemia/reperfusion (I/R) injury, and statins have been reported to exert antioxidant activity. However, the role of VCAM-1 and xanthine oxidase (XO)/uric acid (UA) in ovarian I/R injury is not known. Also, whether or not atorvastatin exerts antioxidant activity like other statins is unclear.Objectives This study investigated the involvement of VCAM-1 and XO/UA in ovarian I/R injury and the likely protective role of atorvastatin.Methods Forty female Wistar rats were randomized into sham-operated, ischaemia, ischaemia/reperfusion (I/R), ischaemia and atorvastatin, and I/R and atorvastatin.Results In comparison with the sham-operated group, atorvastatin blunted ischaemia and I/R-induced distortion of ovarian histoarchitecture and follicular degeneration. Also, atorvastatin alleviated ischaemia and I/R-induced rise in XO, UA, and malondialdehyde, which was accompanied by inhibition of ischaemia and I/R-induced reductions in reduced glutathione level, enzymatic antioxidant activities and increase in myeloperoxidase activity and TNF-α and IL-6 levels by atorvastatin treatment. Additionally, atorvastatin blocked ischaemia and I/R-induced increase in VCAM-1 expression, caspase 3 activity, 8-hydroxydeoxyguanosine level and ovarian DNA fragmentation index.Conclusion For the first time, this study revealed that atorvastatin-mediated downregulation of VCAM-1 and XO/UA/caspase 3 signaling averts oxidative injury, inflammation, and apoptosis induced by ovarian ischaemia/reperfusion injury.